2017
DOI: 10.18632/oncotarget.17633
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells preferentially migrate toward highly oncogenic human hepatocellular carcinoma cells with activated EpCAM signaling

Abstract: The epithelial cell adhesion molecule (EpCAM) is a type I transmembrane glycoprotein that is regarded as one of the markers for tumor initiating cells (TIC) in human hepatocellular carcinoma (HCC). Much work has been directed towards targeting these TICs as a mean of placing these master regulators of cell proliferation and drug resistance under control. Human bone marrow-derived mesenchymal stem cells are known to exhibit an innate property of tumor tropism. However, the possible relationship between MSC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…These findings apply to other cancer tumor-initiating cells such as colorectal, ovarian, and hepatocellular carcinoma CSCs. [57][58][59][60] Also, CSCs EpCAM expression has been associated with therapy resistance and tumor bulk maintenance. 56,58,59,61 Importantly, EpCAM is one of the most reliable markers of circulating tumor cells (CTCs) in various carcinomas, and the presence of EpCAM + CTCs is related to poor outcome, like colorectal cancer, head and neck cancer, ovarian cancer, and breast cancer.…”
Section: Solid Cancermentioning
confidence: 99%
“…These findings apply to other cancer tumor-initiating cells such as colorectal, ovarian, and hepatocellular carcinoma CSCs. [57][58][59][60] Also, CSCs EpCAM expression has been associated with therapy resistance and tumor bulk maintenance. 56,58,59,61 Importantly, EpCAM is one of the most reliable markers of circulating tumor cells (CTCs) in various carcinomas, and the presence of EpCAM + CTCs is related to poor outcome, like colorectal cancer, head and neck cancer, ovarian cancer, and breast cancer.…”
Section: Solid Cancermentioning
confidence: 99%
“…EPCAM (CD326) is an epithelial cell adhesion molecule that plays an important role in the self‐renewal and differentiation of embryonic stem cells. EPCAM‐positive liver cancer cells have self‐renewal and differentiation potential, and form highly invasive tumors in nude mice . In addition, activation of the Wnt‐ β ‐catenin signaling pathway leads to an increase in the number of EPCAM positive cells .…”
Section: Introductionmentioning
confidence: 99%
“…EPCAM-positive liver cancer cells have self-renewal and differentiation potential, and form highly invasive tumors in nude mice. 14 In addition, activation of the Wnt-β-catenin signaling pathway leads to an increase in the number of EPCAM positive cells. 15,16 CD90 + and CD44 + HCC cells demonstrated a more aggressive phenotype.…”
mentioning
confidence: 99%
“…In contrast, down-regulation of EpCAM can inhibit the proliferation and invasion of tumor cells (39). EpCAM is a target gene of the wnt/β-catenin signaling pathway, which is considered a critical marker of tumor cells with the characteristics of stem cells (40). Besides, in vitro studies have also shown that EpCAM is a downstream target gene of transferrelated protein 1, and overexpression of transfer-related protein-1 can increase the expression of EpCAM, leading to enhanced invasion and metastasis of lung cancer (41).…”
Section: Discussionmentioning
confidence: 99%